RETRACTED: Carbon pricing and environmental response: A way forward for China’s carbon and energy market - Wang, Yuchen; Zhou, Xiaoming; Ali, Anis; Omar, Abdullah Bin; Rahman, Zia Ur (Frontiers in Environmental Science, 2022)
Addressing the conflict between fossil fuel exploitation, usage, and greenhouse gas emissions is a top priority for China’s low-carbon socioeconomic development. Scalable Axisymmetric Matrix “a computerized general equilibrium model” is used to assess the impact of carbon tax policies on energy usage, carbon pollution, and macroeconomic drivers at reduction levels of 10%, 20%, and 30% of emissions. In the meantime, we examine the impact of various carbon tax recycling schemes in line with the tax neutrality concept. Although the carbon tax successfully reduces carbon emissions, we conclude that it will have a detrimental effect on the economy and social well-being. To cope with China’s increasing pollution emissions and ecological imbalances, the Chinese government promulgated the environmental protection tax law of the people’s Republic of China, which was officially implemented in 2018. Although carbon dioxide is not included in the Taxable Pollutants and Single Quantity Table attached to this law, China has almost reached a consensus on taxing carbon emissions. In 2021, the State Council of China issued the opinions on completely, accurately, and comprehensively implementing the new development concept and doing a good job in carbon peak and carbon neutralization, which made a comprehensive deployment to achieve the “double carbon” goal and improved the carbon tax policy and legal system, which is an essential part of it. Therefore, based on fiscal neutrality, an effective carbon tax recycling scheme can mitigate the adverse effects of its adoption. However, due to the current development in China’s energy-generating and transportation sectors, even minor steps can have huge effects on emissions with marginal economic implications.